FEMICÍDIO: a (mal) anunciada morte de mulheres - Izabel Solyszko Gomes (Universidade Federal do Maranhão, 2010)
This article is the product of a research conducted for a master’s degree dissertation on the criminal ́s justice system based on the analysis of criminal cases. The discussion focuses the lethal expression of gender violence, that is, murder. The study of crime through the concepts of femicide and legal aspects, and learning about the specific concepts involving the killing of women, that occurred mainly due to sexism as well as the characterization of police performance and legal responses to these cases, allows a process of discovery and understanding of reality. This article considers three factors for analysis: the mortality of women as an expression of gender violence, impunity and the pseudo impartiality of justice.